AIR BRUSH TECHNOLOGY, WEBSITE BRANDING AND CASH FLOW MANAGEMENT IN J-ART MEDAN - Thohiri, Roza; Harahap, Khairunisa; Maulana, Bagoes; Zainal, Andri; Putra, Pasca Dwi (Journal of Community Research and Service, 2019)
This dedication activity is focused on solving the problems that become priority problems, namely the lack of application of appropriate technology tools that can accelerate the process of coloring art products, and good and standardized management and financial strategies and website creation. The partners involved in this activity are J-Art SMEs led by Mr. Faisal Walad. This UMKM is located at Jalan Umar Gg. Karsidi No.70, Glugur Darat I Village, Medan Timur District. The service activities referred to are the provision and assistance of the use of wind compressor machines and spray guns, good management assistance and assistance of manual and electronic financial reports and the provision of website branding. This activity also resulted in several outcomes in the form of TTG implementation, management and financial assistance and a commercial website.Keywords: Air Brush; Management; Finance; Website.